AGAPE SEBAGAI LANDASAN LEARNING LIVE TOGETHER UNTUK MENGEMBANGKAN KARAKTER INDIVIDU, KELUARGA, DAN MASYARAKAT - Jonathan Wantoro (Jurnal Excelsior Pendidikan, 2021)
Abstract: Love is something very vital and it's miles the primary factor of Christian teaching, first. The problem: How are Agape values taught on a foundation? How is Agape the Foundation for getting to know to stay collectively to increase individual, own circle of relatives, and network man or woman? This observation makes use of a qualitative technique with a descriptive approach. Answers: (1) Agape comes from God, God is agape, and the shape of God is agape. The traits of agape love are: patient, generous, now no longer jealous, now no longer smug and smug, now no longer rude, altruistic, forgiving, fair, questioning, and performing undoubtedly due to the fact love is capable to forgive mistakes.  (2) Agape as a foundation for getting to know to stay collectively to increase individual, own circle of relatives, and network characters as a useful resource for someone to stay with others.  The own circle of relatives turns into the right getting-to-know technique of existence. Social existence is a bigger technique wherein someone starts off evolved to take duty for the issues of society via way of means of making use of agape values to emerge as the idea for individual, own circle of relatives, and network man or woman growth.Abstrak: Kasih adalah sesuatu yang sangat penting dan merupakan pokok  ajaran Kristen, yang pertama-tama. Persoalannya: Bagaimanakah nilai-nilai Agape diajarkan dalam kehidupan sehari-hari? Bagaimanakah Agape Sebagai Landasan Learning Live Together untuk Mengembangkan Karakter Individu, Keluarga, dan Masyarakat? Penelitian literature review menghasilkan: (1) Agape berasal dari Tuhan, Tuhan adalah agape dan wujud Tuhan adalah agape.Ciri-ciri kasih agape adalah: sabar, dermawan, tidak cemburu, tidak sombong dan angkuh, tidak berbuat kasar, tidak mementingkan diri sendiri, pengampunan, keadilan, berpikir dan bertindak positif, karena kasih  mampu memaafkan kesalahan. (2) Agape sebagai dasar belajar hidup bersama untuk mengembangkan karakter individu, keluarga, dan masyarakat sebagai sumber daya seseorang untuk dapat hidup bersama  orang lain. Keluarga menjadi proses belajar hidup yang ideal. Hidup bermasyarakat merupakan proses yang lebih luas dalam dimana seseorang mulai bertanggung jawab atas masalah masyarakat dengan menerapkan nilai-nilai agape menjadi dasar  bagi pertumbuhan karakter individu, keluarga, dan masyarakat.